Kronus: sistema web para controle do setor de segurança no trabalho - Silva, Wagner Ediel da (2013)
This work presents the development of a web-based system for control of the security sector in the work to companies that use or want to use technology to make the control environment. For the execution of the work was used for coding object-oriented programming language C # with Framework ASP. NET MVC 4 aided by the IDE Visual Studio 2012 with SQL Server 2008 as the database and relational Framework Bootstrap, used for formatting web pages.